Worldwide distribution of human Y-chromosome haplotypes. - Santos, F R; Bianchi, N O; Pena, S D (Genome Research, 1996)
We surveyed several human populations worldwide with three PCR-based polymorphisms located in the human Y chromosome: the alphoid heteroduplex [alpha(h)] polymorphic system, the DYS19 microsatellite locus, and a polymorphic Alu insertion (YAP). By typing with the former two polymorphisms [alpha(h) and DYS19] we found 46 different haplotypes in 364 males from several populations worldwide. There were significant geographic differences in the distribution of the haplotypes, several of which were seen in only one population and can be used as populational markers in future surveys. The haplotypic diversity in major ethnic groups revealed high levels in Greater Asians, followed by Africans and Caucasians, and a very low diversity was seen in Amerindians. The discrimination probability of such haplotypes for a random sample of Brazilian Caucasians was 0.82, suggesting great potential usefulness in forensic studies. The parsimonious relationship between different alpha(h) types and the addition of the YAP polymorphism data allowed the construction of an informative picture of the origin and evolution of the antiquity of the alpha(h) polymorphism. The DYS19 allele diversity related to each alpha(h) type allowed a crude estimation of the antiquity of many alpha(h) types. These ancient alpha(h) types were present in different populations suggesting a common ancestor that could antedate the first out-of-Africa migrations.